The prevalence of prudence in a risky occupation - Schaap, Robbert (Economics letters, 2021)
In this paper I present the first experimental measurement of prudence with a subject pool that is active in a high-risk occupation. Using a lab-in-the-field experiment I measure the prevalence of prudent preferences among 423 Chilean small-scale fishers. The prevalence of prudence in this sample is significantly lower than that found in previously measured samples. The key findings are that prudence (1) correlates with preferences for more secure occupations and (2) decreases strongly with the tenure and age of the fisher. I show that these findings are robust when controlling for risk aversion. (C) 2021 Elsevier B.V. All rights reserved.